Reverend Mother and Tamar (Gn 38) trapped between "artificial" barrenness and "normative" motherhood: Any fitting biblical hermeneutic? - Masenya, Madipoane J. (HTS teologiese studies, 2019)
Reverend Mother’s entry into ordained ministry did not quench her maternal instinct to experience the fruit of her own body. Her craving was thus not for a man as a husband but for a baby, the fruit of her own womb. As a result of her unconventional choice to fulfil her desire technologically, the church ‘[…] stripped her of her authority, position, and title’ (Henry 2010). In many a family-oriented, communal, hetero-patriarchal (African) Christian setting, a setting in which many a woman, persuaded by a specific biblical hermeneutic, finds herself trapped between ‘artificial’ infertility and a deep desire to have a baby, what kind of hermeneutic may emerge if Genesis 38 is read side by side with Reverend Mother’s narrative? The present article is an attempt to engage the preceding question critically.